Moderating Effect of Message Framing on Interest Adoption toward BYOND by BSI: The Roles of Brand Image and Brand Ambassador - Muhammad Rizky Putra; Muhammad Syahbudi; Nurul Inayah (Jurnal Investasi Islam, 2026)
This study aims to analyze the influence of Brand Image and Brand Ambassador on the Interest Adoption BYOND by BSI services among university students and to examine the role of Message Framing as a moderating variable. Using a quantitative approach using the Moderated Regression Analysis (MRA) method, a sample of 98 respondents was selected using a probability sampling method using proportional stratified random sampling based on student population data in each FEBI UINSU department. The analysis was then processed using the JASP analysis tool. The results of the study indicate that Brand Image and Brand Ambassador each have a positive and significant influence on the Interest Adoption BYOND by BSI services. Together, these two variables are also proven to have a significant influence on the Interest Adoption. However, the results of the moderation test indicate that Message Framing is unable to moderate the influence of Brand Image and Brand Ambassador on the Interest Adoption BYOND by BSI services. The novelty of this study lies in testing the moderating effect of message framing in the context of the adoption of a newly launched Islamic banking super app. The implications of these findings emphasize that student interest is driven independently by the strength of the institution's trustworthy image and the personal appeal of public figures, so that marketing strategies must prioritize functional safety reputation and real credibility over variations in promotional message framing.